10. PRELIMINARY EVALUATION OF THE EFFECTIVENESS OF CHANGING THE NUMBER OF ACNE LESIONS BY COMBINING AURICULAR ACUPUNCTURE AND ADAPALENE APPLICATION IN ACNE TREATMENT AT LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To compare the changes in the number of acne lesions before and after treatment with auricular acupuncture targeting the Endocrine, Subcortex, Lung, Heart, and Stomach points combined with 0.1% adapalene, and to assess the adverse effects of this combination treatment after 4 weeks.Method: A single-group interventional study was conducted to evaluate the effectiveness of auricular acupuncture combined with 0.1% adapalene before and after treatment in 33 acne patients, and to assess adverse effects after 4 weeks of treatment.Results: After 4 weeks of treatment combining auricular acupuncture at the Endocrine, Subcortex, Lung, Heart, and Stomach points with 0.1% adapalene, the number of inflammatory acne lesions significantly decreased from 2 (0-6) to 0 (0-2) (p
Keywords: Acne vulgaris, auricular acupuncture, adapalene